Structural change in Argentina, 1935–60: The role of import substitution and factor endowments - Debowicz, Darío; Segal, Paul (International Food Policy Research Institute, 2012)
This paper investigates structural change in Argentina between 1935 and 1960, a period of rapid industrialization and of relative decline of the agricultural sector. This has been the subject of a long-running debate that has exercised Argentine economists throughout the twentieth century, and remains politically salient today. It has been argued that this this relative decline of agriculture was due to the policies of import-substituting industrialization (ISI). This was also the period, however, that directly followed the closing of the land frontier, resulting in a declining land-labor ratio as the population continued to grow. We use a stylized, dynamic three-sector computable general equilibrium (CGE) model of the period to analyze the respective effects of ISI policies and the observed changes in factor endowments on the structure of the economy. We find that the declining land-labor ratio was more important than ISI in explaining relative stagnation in agriculture. ISI gave a substantial boost to manufacturing but primarily at the expense of nontraded services, rather than of agriculture.